(untitled) - Rozanski, Elizabeth A (London, 2007)
This concise handbook focuses on management of the more common emergency and critical care conditions encountered in practices.There are chapters on each body systems, on toxicology and other environmental causes, and on critical care skills and techniques ranging from patient monitoring, anesthesia and analgesia, to fluid therapy.
Keywords: Cấp cứu thú y,Veterinary emergencies